Political Communication Strategy of the Democratic Party in Winning the Kharisma Pair in the 2024 Pamekasan Regency Election - Syarif Syarifuddin (PT Agung Media Publisher, 2025)
This research focuses on the political communication strategy applied by the DPC of the Pamekasan Democratic Party to win the KHARISMA (KH. Kholilurrahman and Sukriyanto) pair in the 2024 Pilkada. The purpose of this study is to analyze the communication strategies used by the Democratic Party in building voter support amid the dominance of religious parties and strong cultural influences in Pamekasan Regency, as well as identifying factors that support and hinder the implementation of these strategies. The method used in this research is descriptive qualitative with a case study approach. The results showed that the communication strategy implemented by the DPC of the Democratic Party was personal, cultural, and figure-based. The main supporting factors include legitimacy from charismatic pesantren figures, local social networks, and strong religious narratives. Meanwhile, the obstacles faced included the low initial popularity of the candidate pairs and legal disputes at the Constitutional Court. This study concludes that the success of the Democratic Party's political communication is strongly influenced by its ability to adjust its strategy to the socio-cultural structure of Pamekasan society and build inclusive and adaptive political communication.